Quantitative Assessment of Chronic Thalamic Stroke - Pergola, G.; Suchan, B.; Koch, B.; Schwarz, M.; Daum, I.; Güntürkün, O. (American Journal of Neuroradiology, 2013)
SUMMARY: The procedure presented quantitatively assesses thalamic lesions in the chronic phase of an ischemic episode. The structural MR images of 19 patients with ischemia in the thalamus were assessed by radiologic inspection. An independent rater allocated the damage to the thalamic nuclei. The assessments showed 89% accordance with the radiologic inspection (P < .001). This procedure ranks the extent of the damage to thalamic nuclei and accounts for postacute rearrangement of the neural tissue. ILNintralaminar nuclei of the thalamusMDmediodorsal nucleus of the thalamusMIDmidline nuclei of the thalamusPUpulvinarVAventral anterior nucleus of the thalamusVPventroposterior nucleus of the thalamusVLaventrolateral nucleus of the thalamus, anterior portionVMventromedial nucleus of the thalamus